Set of Laws and Decrees on Egyptian federation of construction & building contractors - Egypt (2025)
Decree No.104 of the year 1992 -- Decree No. 205 of the year 1993 -- ministerial Decree No.1 of the year 1993 -- presidential Decree No. 4 of the year 1994